Etude Des Facteurs Affectant Lautilisation Des Technologies Internet Dans Les PME: Cas Du Secteur Manufacturier Tunisien (Global Journal of Management and Business Research, 2015)
This research emphasizes, in a clearer and more differentiating way, the motives or the incentives of the use of the Internet Technologies (IT) by the managers of SME. It is to this problem of the use of the IT in the companies that this communication contributes, via two studies carried out with the managers of the SME Tunisians situated in the regions of big Tunis and Sahel, a quantitative and qualitative study.The results obtained from a qualitative study show globally that the use of the IT within the Tunisian SME is determined by the entrepreneurial and environmental factors.The obtained results, for the method of the structural equations, validate the proposed model by highlighting the entrepreneurial and environmental factors.
Keywords: SME; internet technologies; entrepreneurial factors; environmentalfactors